Hybrid and Collaborative Governance Model for Village Development in Indonesia - Alkadafi, Muammar; Susanti, Susanti; Wasistiono, Sadu; Broto, Mani Festati (Universitas Medan Area, 2025)
Village development in Indonesia continues to face tensions between formal decentralization mandates and persistently centralized governance practices. Although Law Number 6 of 2014 on Villages was intended to strengthen village autonomy, its implementation is often constrained by rigid central regulatory frameworks and standardized fiscal controls, limiting local participation and contextual responsiveness. This study offers a conceptual and empirical contribution by developing and examining an integrated hybrid and collaborative governance model for village development. Employing a qualitative research design, data were collected through in-depth interviews, participatory observation, and document analysis conducted in six villages in Kampar Regency, Riau Province. The findings indicate that hybrid governance, which combines top-down regulatory mechanisms with bottom-up community participation, enhances policy flexibility, responsiveness, and contextual alignment at the village level. Furthermore, the incorporation of collaborative governance strengthens cross-sectoral coordination among central and local governments, village institutions, private actors, and civil society organizations, thereby reducing fragmentation in policy implementation. Theoretically, this study operationalizes hybrid and collaborative governance within the context of village development policy. Practically, it provides policy-relevant insights for strengthening the legitimacy, responsiveness, and sustainability of decentralized governance in Indonesia.